2010
DOI: 10.1002/casp.1037
|View full text |Cite
|
Sign up to set email alerts
|

Keeping the vermin out: Perceived disease threat and ideological orientations as predictors of exclusionary immigration attitudes

Abstract: Integrating evolutionary and social representations theories, the current study examines the relationship between perceived disease threat and exclusionary immigration attitudes in the context of a potential avian influenza pandemic. This large-scale disease provides a realistic context for investigating the link between disease threat and immigration attitudes. The main aim of this cross-sectional study (N ¼ 412) was to explore mechanisms through which perceived chronic and contextual disease threats operate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(90 citation statements)
references
References 61 publications
5
79
0
1
Order By: Relevance
“…The Wave 1 questionnaire was adapted from a previous survey about avian influenza [14]. To homogenize response format, we mainly used Likert scales ranging from 1 to 5 and computed mean scores.…”
Section: Methodsmentioning
confidence: 99%
“…The Wave 1 questionnaire was adapted from a previous survey about avian influenza [14]. To homogenize response format, we mainly used Likert scales ranging from 1 to 5 and computed mean scores.…”
Section: Methodsmentioning
confidence: 99%
“…In terms of Europeans, there is little evidence for widespread levels of worry or for the distancing part of the pattern, in which already marginalised groups are blamed for the cause or spread of a disease. The notion that low threat to humans does not galvanise the age-old pattern is examined by Green et al (2010) via their study of the link between disease threat and exclusion of immigrants in a European context, during the 2005 major international Avian Influenza threat. They found that the threat of disease did not translate directly into prejudice against out-groups in the context of the Avian Influenza threat and suggest that this was because: human-to-human transmission seemed unlikely at the time of the study and so the perceived threat was not strong; although the origin of the outbreak was seen to be Asian, "Bird Flu" was not associated with Asian or other out-groups; instead of being associated with out-groups, the spread was mainly associated with migrating birds and so seen to be beyond human control.…”
Section: When Anxiety Worry and Fear Are Mildmentioning
confidence: 99%
“…As discussed earlier, targets denied mental states (both desires and beliefs) but imputed behavioral potential inspire disgust and fear and are likened to pestilence, cockroaches, parasites, vermin, and other disease‐carriers. Targets of these metaphors include terrorists (Steuter & Wills, , ), homeless individuals (Amster, ), welfare recipients (Gring‐Pemble, p. 350), and immigrants (Green et al, ; O'Brien, ). These groups exhibit behavioral agency through their “swarming” and their ability to transfer contamination and spread disease, but they are denied mental states.…”
Section: The Abc Model's Account Of Dehumanizing Metaphorsmentioning
confidence: 99%